Prevalence and Distribution of Unerupted/Impacted Teeth Among Individuals 18-25 Years of Age Visiting Outpatient Department of Private Dental College and Hospital in Chennai, India - C.S. Yuvashree1 , Pratiba Ramani2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The term unerupted / impacted teeth defines a failure of the tooth to erupt within the expected time into thedental arch. Impaction is a common dental anomaly where the tooth has not erupted beyond the eruptionperiod. The incidence of unerupted / impacted teeth differs among different populations and in differentethnic groups. The aim of this study was to assess the prevalence of unerupted/ impacted teeth amongpatients of 18-25 years of age visiting Private Dental college and hospital, Chennai. This is a descriptivestudy which is performed under a university setting where all the patients reported to Private Dental collegeand hospital, chennai. The data was collected by reviewing patients records and analysed the data of 86000patients who underwent extraction between June 2019 to March 2020. The population size of the study wasfound to be n=296 .Data was collected , tabulated ,statistical analysis was done by SPSS – IBM.( StatisticalPackage for Social Studies ). From the statistical analysis, it is observed that the total number of extractiondone between 18-25 years was found to be n=7339 (96%) out of which only n= 295 (4%) was found with anincidence of impaction. The overall prevalence of unerupted/ impacted teeth were higher in males(55.74%)predominantly between the age groups of 24 years (18.8%) and was commonly reported to third molars(41.9%). Within the limitation of the current study, it is found that unerupted / impacted teeth are morecommon among 24 years of age with male predilection with higher incidence of mandibular molars.